A review on thermal and catalytic pyrolysis of plastic solid waste (PSW). (15th July 2017) - Al-Salem, S.M.; Antelava, A.; Constantinou, A.; Manos, G.; Dutta, A.
Abstract: Plastic plays an important role in our daily lives due to its versatility, light weight and low production cost. Plastics became essential in many sectors such as construction, medical, engineering applications, automotive, aerospace, etc. In addition, economic growth and development also increased our demand and dependency on plastics which leads to its accumulation in landfills imposing risk on human health, animals and cause environmental pollution problems such as ground water contamination, sanitary related issues, etc. Hence, a sustainable and an efficient plastic waste treatment is essential to avoid such issues. Pyrolysis is a thermo-chemical plastic waste treatment technique which can solve such pollution problems, as well as, recover valuable energy and products such as oil and gas. Pyrolysis of plastic solid waste (PSW) has gained importance due to having better advantages towards environmental pollution and reduction of carbon footprint of plastic products by minimizing the emissions of carbon monoxide and carbon dioxide compared to combustion and gasification. This paper presents the existing techniques of pyrolysis, the parameters which affect the products yield and selectivity and identify major research gaps in this technology. The influence of different catalysts on the process as well as review and comparative assessment of pyrolysis with other thermal and catalytic plastic treatment methods, is also presented. Highlights: We review the technology of pyrolysis, detailing the main influencing factors. Typical setups are detailed showcasing main engineering aspects and feedstock type. Analytical/applied pyrolysis with a focus on catalytic performance is detailed.